Is It Learning or Scutwork? Medical Students Adding Value in the Emergency Department. Issue 1 (27th November 2018) - Griffith, Max; Santen, Sally A.; Allan, Jack; Leumas, Jordan; Grace, Kelsey; Lewis, Nathan; Peterson, William J.
Abstract: In busy emergency departments (EDs), it can be difficult for faculty to teach students amid pressure to provide patient care and conduct research. As a result, medical student teaching may be an afterthought rather than a priority, and there is a lack of focus on how students spend their time during clinical shifts in the ED. Students want to contribute to departmental workflow, but can be hampered by systems limitations and lack of clinical knowledge. One solution is for faculty and medical students to partner to add value to patient care in the ED. However, faculty and students must be wary of the distinction between activities that add value and "scutwork, " tasks that involve little learning and do not require medical expertise. In this perspective, the student, resident, and faculty authors discuss learner and educator perspectives for how medical students can be productive contributors to patient care in the ED without being subjected to scutwork. They also recommend ideas for productive student activities that promote learning, contrasted with examples of scutwork to avoid. Definitions of value‐added activities and scutwork depend on the learner's experience level and interests and are subject to debate. However, if medical students can be engaged in learning while also providing meaningful contributions to patient care, students, educators, and patients stand to benefit.